Impact of the Healthstyles health promotion program on health care utilization: A secondary analysis of data. - Cousins, Margaret. (University of Ottawa (Canada), 1994)
Healthstyles was a community based health promotion program that ran in Ottawa from 1982 to 1984. This program provided an opportunity to assess the effects of health promotion on health behaviours and use of health care services through a quasi-experimental design. Primary analyses of questionnaire responses have shown a number of positive behavioural outcomes. For the secondary analysis, data on health care use 6 months before, 18 months during and 6 months after the program were obtained from Ontario's universal health insurance plan (OHIP). These data were available for 520 volunteer participants and 932 matched controls. Participants and controls were matched on sex, age (within 5 years), education level (2 categories), stress (3 levels), smoking status and an aggregate risk score. Controlling for baseline differences through analysis of covariance, program participants had higher costs and number of visits for ambulatory care during the first year (p 0.01) and second year (p 0.05) after entry into the program. Within ambulatory care, participants used significantly more diagnostic services than controls during both years of follow-up. Participants were also more likely to use counselling and psychotherapy services in year 1 (RR 1.53, 95% CI 1.28, 1.81) and year 2 (RR 1.57, 95% CI 1.31, 1.89). There were no differences between participants and controls in visits for medical consultations and assessments, preventive services or surgical services. These results suggest that health promotion may lead to increased costs and use of ambulatory services, at least over the short-term. However, these costs may be offset over a longer follow-up period if health promotion successfully reduces the incidence of chronic illness. Since the sample population was relatively young and had positive health behaviours at baseline, compared to the general population, the results may not apply to other, less healthy populations.
Keywords: Health Sciences, Public Health.